SLAU2 applied to two-dimensional, ideal magnetohydrodynamics simulations. (15th September 2020) - Kitamura, Keiichi; Mamashita, Tomohiro; Ryu, Dongsu
Highlights: SLAU2 flux function extended for 1D MHD (2019) has been applied to 2D MHD. SLAU2 demonstrated comparable solutions to HLLD and higher resolutions than HLL. This work will be an important milestone for further developments of MHD solvers. Abstract: SLAU2 (Simple Low-dissipation Advection-Upstream-splitting-method 2) numerical flux function, one of AUSM-type methods (3-wave solver), originally developed and widely used in gasdynamics, has been applied to two-dimensional magnetohydrodynamics (MHD) simulations. According to numerical tests for a wide range of flow and magnetic conditions, its reliability, efficiency, and accuracy have been demonstrated: i) Robustness of SLAU2 against shock-anomalies (e.g., carbuncle phenomena) has been confirmed in the MHD-extended version of our hypersonic flow test; ii) The computational cost has been reduced for approximately 3% compared with HLLD (Harten-Lax-van_Leer with Discontinuities), a more expensive, 5-wave solver; iii) Nevertheless, its solution qualities are almost equal to those of HLLD, as opposed to very diffused HLL solutions. For benchmark tests, detailed and important flow physics such as multidimensional shock/shock interactions have been successfully reproduced by SLAU2. We hope that SLAU2 will contribute to further progress of the astrophysics and other research fields.